1991
DOI: 10.1007/bf00760799
|View full text |Cite
|
Sign up to set email alerts
|

Strength characteristics of a healthy urban adult population

Abstract: A random sample of 778 subjects representing ages 25, 35, 45 and 55 years were studied for the amount of habitual physical activity, their anthropometric structure, vertical jumping height, trunk extension and flexion torques and dynamic endurance fitness of trunk extension and flexion. The proportion of subjects who were habitually physically active did not change systematically with age. The highest number of physically inactive subjects was found in men and women in the 35-year age group. The results in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 14 publications
0
23
1
2
Order By: Relevance
“…Furthermore, a recent study, which compared the static Sorensen test with its dynamic variant, revealed that the latter was less comfortable and more difficult to standardize (Demoulin et al, 2008b). In a few studies, the subjects were asked to perform as many repetitions as possible in 30 seconds (Viljanen et al, 1991;Kujala et al, 1996). …”
Section: Dynamic Tests ("Arch-up Tests")mentioning
confidence: 99%
“…Furthermore, a recent study, which compared the static Sorensen test with its dynamic variant, revealed that the latter was less comfortable and more difficult to standardize (Demoulin et al, 2008b). In a few studies, the subjects were asked to perform as many repetitions as possible in 30 seconds (Viljanen et al, 1991;Kujala et al, 1996). …”
Section: Dynamic Tests ("Arch-up Tests")mentioning
confidence: 99%
“…As there are substantial differences in physical capacity between men and women Rogol et al 2000;Viljanen et al 1991;Åstrand 1997) the analyses were performed separately. By using box plot analyses, extreme outliers (defined as values exceeding the distance between median and quartile values more than three times) were identified and excluded from further analyses.…”
Section: Data Analysesmentioning
confidence: 99%
“…[16][17][18] The same physiotherapist (MK) tested all patients. She also instructed and supervised the physiotherapy students who ran the tests on control subjects at their schools.…”
Section: Tests For Physical Performancementioning
confidence: 99%